A ball head positioning method based on hybrid force-position control. (September 2021) - Chu, Wenmin; Huang, Xiang; Li, Shuanggao; Lou, Peihuang
In the digital aircraft assembly system, the large component of aircraft is connected with the numerical control locator through a ball joint composed of a ball head and a ball socket. To ensure the posture adjustment accuracy of large component of aircraft, the clearance between the ball head and the ball socket is very small. Therefore, it is very difficult to accurately guide the ball head of large component of aircraft into the ball socket of the numerical control locator. Aiming at this problem, this article proposes a ball head positioning method based on hybrid force-position control, so that the ball socket can approach the ball head adaptively. First, according to the technical characteristics of the ball head positioning, the axes of the numerical control locator are divided into position control axis and force control axis, and the conditions to ensure the safety of ball head positioning are analyzed. Then the control model of ball head positioning based on hybrid force-position control is established and simulated by Simulink. Finally, a simulated posture adjustment system is built in the laboratory, and a series of ball head positioning experiments based on hybrid force-position control are carried out. The experimental results show that, compared with the traditional ball head positioning method, the ball head positioning process based on hybrid force-position control is more stable and faster, and the method can significantly reduce the lateral force. Moreover, the proposed method can be easily integrated into the existing posture adjustment system without additional hardware cost.